Rekonstruktivna kirurgija zgornjega uda in rehabilitacija pri bolnikih z okvaro vratne hrbtenjače - Polončič, Petra (Rehabilitacija (Ljubljana), 2018)
Reconstructive upper limb surgery is a method that potentially improves upper limb function in carefully selected patients with cervical spinal cord lesion, increasing their functional independence and quality of life. In some countries, it is a standard part of the rehabilitation protocol with organised surgical services and a tight cooperation of the operative and rehabilitation teams. The aim of this review is to present reconstructive upper limb surgery possibilities in patients with tetraplegia, the selection and assessment of appropriate candidates, postoperative rehabilitation and foreign countries results. The discussion describes the possibilities of implementing the program in our country.
Keywords: funkcija; nerve transfer; paraplegija; presaditev tetiv; presaditev živcev; reconstructive hand surgery; Reconstructive Surgical Procedures; rehabilitation; rekonstruktivna kirurgija; Spinal Cord Injuries; tendon transfer; tetraplegia; upper limb; zgornji ud